(untitled) (Innovaciones Educativas, 2022)
Life skills are indispensable for a student’s future performance, so it is essential to evaluate the degree to which they are developed through the academic curriculum. The present study explores how much the perceptions of teachers, monitors, and students coincide about the life skills they develop in four elective courses at Universidad del Rosario - Colombia. Perceptions were obtained through three different collection methods: focus groups, participatory observation, and a questionnaire. The results showed a percentage of agreement among the participants on which skills are developed of 34.8% in the Oenology elective class, 55% in the Creative Writing Workshop, 80% in an elective class focused on stress management, and 94% in the Map of Senses elective class (general agreement 66%). In the end, it is discussed that, while it is true that the elective classes’ focus is to achieve not only an education for the academic world but also for real life. Therefore, it is necessary to adjust in a prior and measurable way which are the skills to be developed in each subject and in what way, in order to optimize learning outcomes and have an impact concomitant to the courses’ objectives. The results showed a 66% agreement among the participants leading to the discussion that, although it is true that the electives are adequately focusing on education for life and not only for academia, it is necessary to standardize in advance and measure what skills are developed in each subject and in what way, to optimize learning results and have an impact according to the objectives of the subjects.